Deadly medicine Indians and alcohol in early America - Mancall, Peter C. 1959- (Cornell Univ. Press, 1995)
Forever shattering the stereotype of the drunken Indian, Mancall offers a powerful indictment of English participation in the liquor trade and a new awareness of the trade's tragic cost for the American Indians